Supported Playgroups for Health Promotion Activity for Healthy Eating and Active Living: A Social Ecological Perspective. Issue 1 (March 2017) - Lloyd, Beverley; Buffett, Kym M.; Innes-Hughes, Christine; Jackson, Dianne; Qi, Jing; Powell, Libby
CHILDHOOD OVERWEIGHT PROBLEMS AND obesity is a significant problem in Australia, with 19 per cent of children commencing kindergarten either overweight or obese. The issue is increasingly recognised within both health promotion and the early childhood education and care sectors. The purpose of this paper is to identify a health promotion approach appropriate for supported playgroups—facilitated playgroups targeting vulnerable families. Primary research included individual interviews with managers, facilitators and parents/carers and observations within four non-specialist supported playgroups in urban and regional locations in NSW. Our findings show that supported playgroups lend themselves to the integration of healthy eating and active play with current practice, building on the existing methods and strengths of supported playgroups rather than additional intensive programming. They provide a 'soft entry' vehicle to deliver a health promoting environment, play-based learning activities for children and context-specific participatory and implicit learning for parents and carers.